Bioprospeksi ekstrak jahe gajah sebagai anti-crd: kajian aktivitas antibakteri terhadap Mycoplasma galliseptikum dan e. coli in vitro - Min Rahminiwati; Aulia Andi Mustika P.; Siti Saadah; . Andriyanto; . Soeripto; Unang P. (Institut Pertanian Bogor, 2010)
CRD is chronic respiratory disease in chicken caused by infection of Mycoplasma gallisepticum (M gallisepticum) and E. coli. Rio-prospective of jahe for controlling the disease was investigated through the study of antibacterial activity against M. gallisepticum of fresh ginger juice extract and fraction of hexan, ethyl acetate, methanol and water against M. gallisepticum and E. coli. The results showed that the juice of fresh ginger inhibited the growth of M. gallisepticum with the minimum inhibitory concentration that could inhibit the growth was 10 °/o. The fractions that effectively inhibited the growth of M. gal/isepticum are hexan fraction and water fraction with the smallest inhibition zone was found at concentration of at least 8 % and 10 % respectivelly.TLC examination results of hexan fraction showed a purple spot with Rf value of 0.9 and a dark blue spot with Rf value of 0.36. Based on Rf values and color reference, the first spot was suggested zingiberen and the second spot was gingerol. All fractions that were examined, did not show any inhibitory activity against thegrowth of E coli. Thus the extract of fresh ginger was only to be used to control the respiratory disease causedby M. gallisepticum but not coli.